Minimum Wage Level and The Number of Jobs in Malaysia - Ali, Maimunah (Research in Management of Technology and Business, 2020)
This study aims to assess the implementation of the minimum wage level on the number of jobs offered in Malaysia. Gazetted by the Minimum Wages Consultative Council in 2011, the gazette became law in 2013. Economic theories suggest that the implementation of the minimum wage law would alleviate the unemployment level in a country due to the reduction in vacancies and job placement being offered by employers to avoid incurring higher production cost. Therefore, this employs analysis of time-series data from JobsMalaysia website and the minimum wage level to ascertain the effect of the minimum wage level on the the number of total jobs offered in Malaysia before and after the implementation of the Minimum Wage Act 2013. The results show that the minimum wage level has little or insignificant effect on the number of jobs offered in Malaysia.